2020
DOI: 10.14744/nci.2020.70037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Among Children in a Training and Research Hospital Clinic in Istanbul and Comparison with Updated Sydney Classification Criteria

Abstract: OBJECTIVE:Helicobacter pylori (H. pylori) is a gram-negative bacterium and one of the reasons for gastritis, peptic and duodenal ulcers. It is a crucial public health problem for both children and adults, especially in developing countries. This study aims to investigate the prevalence of Helicobacter pylori positivity in children and to compare with updated Sydney classification criteria. METHODS:This study was conducted from January 2015 to June 2017. This study included 885 children aged 0-17 year(s). Endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…However, the prevalence of infection in other Polish studies is similar and confirms the obtained results [18,19]. Interestingly, the prevalence of HP infection in the control group of Oztürk et al [10] was significantly different (9.4%) than that in two large groups of children (n = 885 and n = 101) studied in Turkey (63.2% and 47.2%, respectively), based upon a histopathological assessment [20,21]. Although the prevalence of gastritis/esophagitis was suggested to be higher in American adult patients with PKU [4], gastritis and duodenitis were not documented to be more frequent in German patients [5] as compared to the prevalence of gastritis/esophagitis in healthy controls.…”
Section: Discussionsupporting
confidence: 84%
“…However, the prevalence of infection in other Polish studies is similar and confirms the obtained results [18,19]. Interestingly, the prevalence of HP infection in the control group of Oztürk et al [10] was significantly different (9.4%) than that in two large groups of children (n = 885 and n = 101) studied in Turkey (63.2% and 47.2%, respectively), based upon a histopathological assessment [20,21]. Although the prevalence of gastritis/esophagitis was suggested to be higher in American adult patients with PKU [4], gastritis and duodenitis were not documented to be more frequent in German patients [5] as compared to the prevalence of gastritis/esophagitis in healthy controls.…”
Section: Discussionsupporting
confidence: 84%
“…In the survey carried out by Ozbey et al, antral nodularity was detected in 54.5% of the children, and 76.4% of them had a positive result for H. pylori [31]. Several studies with variable percentages of endoscopic nodularity in pediatric patients support the correlation between H. pylori infection and the endoscopic appearance of nodular gastritis [32]. Kalach et al performed a meta-analysis on the histopathological aspects of gastric biopsy according to the Sydney System in children, which revealed that there was a higher risk of chronic inflammation, and atrophy occurred rarely [33].…”
Section: Discussionmentioning
confidence: 95%
“…Sus resultados muestran que el 20% de los infectados con H. pylori, desarrollan patologías gastrointestinales relacionadas al sistema digestivo medio y encontraron una asociación estadísticamente significativa entre las patologías y la evidencia histológica de H. pylori (p=0,031). Calim y col. (32) evaluaron los resultados clínicos de 885 niños de 0 a 17 años que habían acudido al servicio de gastroenterología de un hospital de Turquía. Sus hallazgos mostraron que 418 (47,2%) fueron positivos para H. pylori y que la pangastritis eritematosa y la nodularidad antral tuvieron una correlación con la infección.…”
Section: /9unclassified